Effects of the Length and Location Heat Source on the Assisting Mixed Convection in A Channel Attached to Parallelogram Cavity - Hussein, Amal Abdul Razaq Abdul; Hussein, Ahmed Kadhim (International Journal of Membrane Science and Technology, 2023)
The current research presents a numerical investigate of the effect of the heat source length and location on the mixed convection aiding flow inside the horizontal channel attached with an open parallelogram cavity .When the heated wall is on the same side of the force inflow .The heat source length was considered as (?) (0.25< ? <1) with a different in the location of the heat source on sidewalls of the cavity. The cold airflow and fixed velocity enter the channel horizontally. The vertical walls in the inflow and outflow sides are isothermal while all other walls are adiabatic. The flow and thermal fields computed for a wide range of Richardson numbers (Ri=0.1-100). While, both Reynolds and Prandtl numbers are kept constant at (Re = 100) and (Pr = 0.71). The results were presented of the flow and thermal fields, average Nusselt numbers. The results show that a rate of heat transfer is increase with in increasing in Richardson numbers (Ri) and the length of the heat source(?). Also, it was found that, the maximum average Nusselt number is achieved in the upper region of the right wall of the cavity for all values of Richardson number